Induced Mutagenesis in UGT74S1 Gene Leads to Stable New Flax Lines with Altered Secoisolariciresinol Diglucoside (SDG) Profiles - Fofana, Bourlaye; Ghose, Kaushik; Somalraju, Ashok; McCallum, Jason; Main, David; Deyholos, Michael K.; Rowland, Gordon G.; Cloutier, Sylvie (Frontiers in Plant Science, 2017)
Flax secoisolariciresinol (SECO) diglucoside (SDG) lignan is an emerging natural product purported to prevent chronic diseases in humans. SECO, the aglycone form of SDG, has shown higher intestinal cell absorption but it is not accumulated naturally in planta. Recently, we have identified and characterized a UDP-glucosyltransferase gene, UGT74S1, that glucosylates SECO into its monoglucoside (SMG) and SDG forms when expressed in yeast. However, whether this gene is unique in controlling SECO glucosylation into SDG in planta is unclear. Here, we report on the use of UGT74S1 in reverse and forward genetics to characterize an ethyl methane sulfonate (EMS) mutagenized flax population from cultivar CDC Bethune and consisting of 1996 M2 families. EMS mutagenesis generated 73 SNP variants causing 79 mutational events in the UGT74S1 exonic regions of 93 M2 families. The mutation frequency in the exonic regions was determined to be one per 28 Kb. Of these mutations, 13 homozygous missense mutations and two homozygous nonsense mutations were observed and all were transmitted into the M3 and M4 generations. Forward genetics screening of the population showed homozygous nonsense mutants completely lacking SDG biosynthesis while the production of SMG was observed only in a subset of the M4 lines. Heterozygous or homozygous M4 missense mutants displayed a wide range of SDG levels, some being greater than those of CDC Bethune. No additional deleterious mutations were detected in these mutant lines using a panel of 10 other genes potentially involved in the lignan biosynthesis. This study provides further evidence that UGT74S1 is unique in controlling SDG formation from SECO and it is the first report of non-transgenic flax germplasm with simultaneous knockout of SDG and presence of SMG in planta.